Mothers' Coping Strategies for Children with Autism Spectrum Disorder - Nurwianingsih, Marti; Rahmadani, Ni Kadek Aris (Universitas Negeri Semarang, 2024)
Autism is a severe developmental disorder that occurs throughout life, but this behavior can be reduced with proper handling and care from parents, family, and society. The right efforts made to autistic children will affect their growth and development to be better and more useful. The family, especially the mother, is a very important figure who influences the process of child growth and development. Mothers who educate and care for children with warmth will certainly have a more positive impact on children compared to mothers who do it as a duty or just an obligation without involving warmth. The purpose of this study was to determine the coping strategies of mothers who have autistic children and to determine the factors that influence coping strategies. This study uses a qualitative method. The subjects of the study or someone who provides information are mothers who have early childhood children and their neighbors by conducting interviews. Based on the results of the research and discussion that have been carried out, it can be concluded that the coping strategies used are problem focus coping in the form of exercised (cautiousness), emotional focus coping which is done by changing thoughts from being disappointed and sad and finally becoming an acceptance which is done by finding the meaning of the failure experienced by themselves and trying to be grateful (seeking meaning) and another form is escape avoidance or avoiding oneself, which is done in the early days when their child was diagnosed with autism which then tries to grow awareness of oneself of responsibility for the child (accepting responsibility). Factors that influence coping strategies are internal factors and external factors. Internal factors that influence are age and self-awareness of responsibility as a mother. The external factors are family support or social support, education level and economic conditions